Transitioning From Preclinical Evidence to Advanced Therapy Medicinal Product: A Spanish Experience - Gastelurrutia, Paloma; Prat-Vidal, Cristina; Vives, Joaquim; Coll, Ruth; Bayes-Genis, Antoni; Gálvez-Montón, Carolina (Frontiers in Cardiovascular Medicine, 2021)
A systematic and ordered product development program, in compliance with current quality and regulatory standards, increases the likelihood of yielding a successful advanced therapy medicinal product (ATMP) for clinical use as safe and effective therapy. As this is a novel field, little accurate information is available regarding the steps to be followed, and the information to be produced to support the development and use of an ATMP. Notably, successful clinical translation can be somewhat cumbersome for academic researchers. In this article, we have provided a summary of the available information, supported by our experience in Spain throughout the development of an ATMP for myocardial infarction, from the pre-clinical stage to phase I clinical trial approval.